Culture of seagrass, Halophila major (Zoll.) Miquel on different substrates - Kamaruzaman, Fatin Nur Khairiyah (2018)
Seagrass is a valuable primary producer in marine environment. Unfortunately, population of seagrass is declining worldwide including population in Malaysia. The seagrass in Merambong and Tanjung Adang Laut shoals also facing diminishing of seagrass beds in the area due to reclamation activities. Halophila major is new record discovered in the area thus study on this species was performed. Seagrass was propagated using rhizome in different substrates, native substrate from Merambong shoal A, Teluk Kemang and Blue Lagoon and study was conducted at i-Aquas (International Institute of Aquaculture and Aquatic Sciences), Port Dickson. Observation on morphological characteristics and growth performance of Halophila major cultured in different substrates was done in 20 weeks. Water parameter in culture tank was higher than in Merambong A and Tanjung Adang Laut shoals which temperature (31.0.0±0 ºC), Total Dissolved Solid (32045.00±54 mg/L), salinity (32.10±0.14 psu), pH (8.25±0.18), visibility (1.0±0.2 m), and nitrate (84.2±0.4 mg/L). Soil analysis of the substrate showed that the native substrate (Merambong shoal A) can be categorised as loamy sand while the substrate from Teluk Kemang and Blue Lagoon are sand. Morphology of Halophila major from wild and cultured showed similar characteristics of oval shape, rounded leaf tip and green in colour. Through observation during culture period, the plant has covered almost 50% of the substrate area and growth performance was suitable in the native substrate. Growth performance of Halophila major cultured in different substrates showed significant differences in each treatment (p<0.05). The first 4 weeks of cultured Halophila major showed increased in leaf length for each 2 weeks. The plant shed their leaf and produce new shoot within 2 weeks. Leaf dimensions of the seagrass plants showed greater growth and development in the native substrate (control) with the highest leaf length (2.98±0.06 cm) and leaf width (1.85±0.05 cm).